Decolonial Rhetoric of Indigenous Tharu Homestays in Nepal - Bhusal, Purna Chandra (Journal of Innovation in Academia, 2023)
The Tharu, an indigenous people residing in the southern plainland region known as the Terai in Nepal, have a historical memory of marginalization, displacement, and internal colonization. In the past decade, the emergence of homestay businesses among the Tharu has not only provided economic opportunities but has also played a crucial role in promoting their indigenous identity. Building on this phenomenon, this article investigates Tharu homestays in Nepal, with the aim of assessing the ways in which they embody indigenous decolonial rhetoric. Using a qualitative e-research method (Salmons, 2022), this article collects, analyzes, and interprets digital sources such as websites, online newspapers, YouTube videos, Facebook updates, and official reports. The interpretation is grounded in the theoretical framework of indigenous decolonial delinking (Mignolo, 2012; Smith, 2021). The article elaborates on how indigenous Tharu homestays function as decolonial spaces through six distinct lenses: their portrayal in national news coverage, their cartographic presence on Google Maps, their web-based territoriality, indigenous settings, the embodiment of indigenous culture and culinary traditions, and their amplified presence in the socio-digital media. In conclusion, the article finds that indigenous Tharu homestays in Nepal embody decolonial rhetoric by creating an amplified presence of indigenous Tharu identity across multiple spaces. This research contributes to the discourse of indigenous rhetoric, advocating for the protection and promotion of Tharu homestays in Nepal and emphasizing their role in the process of indigenous decolonization.